Obesity and outcomes in patients treated with chemoradiotherapy for esophageal carcinoma. Issue 2 (1st March 2014) - Wang, J.; Myles, B.; Wei, C.; Chang, J. Y.; Hofstetter, W. L.; Ajani, J. A.; Swisher, S. G.; Cox, J. D.; Komaki, R.; Liao, Z.; Lin, S. H.
Summary: Body mass index (BMI ) is a risk factor for comorbid illnesses and cancer development. It was hypothesized that obesity status affects disease outcomes and treatment-related toxicities in esophageal cancer patients treated with chemoradiotherapy (CRT ). From M arch 2002 to A pril 2010, 405 patients with non-metastatic esophageal carcinoma at MD A nderson C ancer C enter treated with either definitive or neoadjuvant CRT were retrospectively analyzed. Patients were categorized as either obese (BMI ≥ 25 kg/m 2 ) or nonobese (BMI < 25 kg/m 2 ). Progression-free survival and overall survival times were examined using the K aplan–M eier method and C ox proportional hazards regression analysis. One hundred fifteen (28.4%) patients were classified as nonobese and 290 (71.6%) as obese. Obese patients were more likely than others to have several comorbid diseases ( P < 0.001), adenocarcinoma located distally ( P < 0.001), and have undergone surgery ( P = 0.004). Obesity was not associated with either worse operative morbidity/mortality ( P > 0.05) or worse positron emission tomography tumor response ( P = 0.46) on univariate analysis, nor with worse pathologic complete response ( P = 0.98) on multivariate analysis. There was also no difference in overall survival, locoregional control, or metastasis-free survival between obese and nonobese patients ( P = 0.86). However, higher BMI was associated with reduced risk of chemoradiation-induced high-grade esophagitis ( P = 0.021), esophageal stricture ( P < 0.001), and high-grade hematologic toxicity ( P < 0.001). In esophageal cancer patients treated with CRT, obesity is not predictive of poorer disease outcomes or operative morbidities; instead, data suggest it may be associated with decreased risk of acute chemotherapy- and radiotherapy-related treatment toxicities.